ANALISIS PENGARUH LINGKUNGAN KERJA DAN STRES KERJA TERHADAP KINERJA KARYAWAN (STUDI PADA BPJS KESEHATAN KC MALANG) - Darmaputra, Henry Aditya (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
The objective of this research, which was conducted at BPJS Kesehatan Branch of Malang, is to analyze both simultaneous and partial influence of work environment and job stress on the performance of employees of BPJS Kesehatan Branch of Malang. Using quantitative approach, this explanatory research aims to explain the causal relation between independent and dependent variables through hypothesis testing. The population of this research is all 72 employees of BPJS Kesehatan Branch of Malang, who were used also as the respondents. The data of this study were collected through questionnaires, interviews, observation, and literature research. The analytical tools of this study are descriptive analysis and multiple linear regression analysis, with F test and t test to test the research hypothesis. The result of the F test indicates that work environment and job stress simultaneously affect employee performance. The result of the t test indicates that work environment and job stress partially affect employee performance. Work environment has a positive beta coefficient, which means that improvement in the condition of work environment will increase employee performance. Job stress has a negative beta coefficient, which means that increased job stress will degrade employee performance.Keywords: Work Environment, Job Stress, and Employee Performance.